Discursive representations of difference and multilingualism in Himalaya with Michael Palin. Issue 3 (3rd July 2019) - Sharma, Bal Krishna
ABSTRACT: In this article, I discuss how mediatised tourism constructs various discourses of othering through representations of the 'tourist self' vis-à-vis the 'local other'. In order to do so, I analyze a six-hour travelogue Himalaya with Michael Palin broadcast by the BBC in 2004. The analysis shows that despite the forces of globalisation that have made national and cultural boundaries more porous than ever before, common stereotypes about otherness continue to shape the experience of travel narratives at present. While the liberal discourses used in the travelogue appear to celebrate the linguistic and cultural diversity of the world, they simultaneously reproduce the moral superiority of the West when the traveller is presented as an authority to give the judgmental accounts of otherness under the guise of equality and tolerance. Himalaya with Michael Palin as a form of mediatised tourism does in fact invoke cultural stereotypes to commodify local authenticities, languages, and identities in order to make the travelogue a 'good' TV programme.